(untitled) - Spuy, Rex van der (New York, NY, 2015)
How do you make a video game? [This book] is a down to earth education in how to make video games from scratch, using the powerful HTML5 and JavaScript technologies. [It] is a point-by-point round up of all the essential techniques that every game designer needs to know. You'll discover how how to create and render game graphics, add interactivity, sound, and animation. You'll learn how to build your own custom game engine with reusable components so that you can quickly develop games with maximum impact and minimum code. You'll also learn the secrets of vector math and advanced collision detection techniqes, all of which are covered in a friendly and non-technical manner. You'll find detailed working examples, with hundreds of illustrations and thousands of lines of source code that you can freely adapt for your own projects. All the math and programming techniques are elaborately explained and examples are open-ended to encourage you to think of original ways to use these techniques in your own games. You can use what tou learn in this book to make games for desktops, mobile phones, tablets, or the Web. [This book] is a great next step for experienced programmers or ambitious beginners who already have some JavaScript experience, and want to jump head first into the world of video game development. ... The game examples in this book use pure JavaScript, so you can code as close to the metal as possible without having to be dependent on any limiting frameworks or game engines. No libraries, no dependencies, no third-party plugins: just you, your computer, and the code. If you're looking for a book to take your game design skills into the stratosphere and beyond, this is it!
Keywords: JavaScript,Trò chơi máy tính,Computer games,JavaScript (Computer program language); Ngôn ngữ lập trình máy tính,Thiết kế,Design